2017
DOI: 10.1515/folmed-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Comorbidity Pattern of Patients with Critical Limb Ischemia

Abstract: Aim: The present study aimed at identifying the pattern of patients with critical limb ischemia (CLI) compared with those with peripheral arterial occlusive disease (PAOD). Materials and methods: A four-year retrospective study was conducted with patients hospitalized in the Second Surgical Clinic at the Emergency County Hospital Cluj-Napoca. The medical charts of patients with PAOD (n=466) and CLI (n=223) were reviewed and data were collected. Results: The study included 689 patients; mean age 67 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…PAD is considered as a serious atherosclerosis-related disease that can lead to frequent hospitalisations, higher health economic cost, a poor quality of life and an increased mortality rate. [14][15][16] Although PAD definition is that of atherosclerosis of the arteries outside the heart, the term is most commonly used to describe occlusive arterial disease of the lower extremities. 17 Similar to other atherosclerotic diseases, PAD is associated with the presence of traditional cardiovascular risk factors, including DM, hypertension, dyslipidaemia, obesity and tobacco consumption.…”
Section: Resultsmentioning
confidence: 99%
“…PAD is considered as a serious atherosclerosis-related disease that can lead to frequent hospitalisations, higher health economic cost, a poor quality of life and an increased mortality rate. [14][15][16] Although PAD definition is that of atherosclerosis of the arteries outside the heart, the term is most commonly used to describe occlusive arterial disease of the lower extremities. 17 Similar to other atherosclerotic diseases, PAD is associated with the presence of traditional cardiovascular risk factors, including DM, hypertension, dyslipidaemia, obesity and tobacco consumption.…”
Section: Resultsmentioning
confidence: 99%
“…11 The mean age of the patients evaluated was similar to that reported in studies by Peña-Corte´s et al, Karles-Ernotte et al, and Lawell et al, which had similar populations (72 to 74.5 years); however, these studies had a greater proportion of men, which did not occur in our series of cases, which had a symmetric distribution in both sexes. 9,[12][13][14][15] The discrepancy in results may be related to the high cardiovascular risk and increased peripheral arterial damage in the elderly female population of Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Goodney et al reported an amputation rate of more than 23 per 10,000 Medicare patients with the peripheral arterial disease (PAD) in Florence, South Carolina [6]. Certain factors, such as age, gender, race, co-existing diseases, smoking, and socioeconomic status, among others, have been associated with higher rates of amputation [6,[8][9][10][11][12]. For example, Ciocan et al identified age as a risk factor for amputation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Certain factors, such as age, gender, race, co-existing diseases, smoking, and socioeconomic status, among others, have been associated with higher rates of amputation [6,[8][9][10][11][12]. For example, Ciocan et al identified age as a risk factor for amputation [8]. Arya et al found the race to be independently predictive of major limb amputation in patients with PAD [11].…”
Section: Introductionmentioning
confidence: 99%